TRADISI PEUCICAP DITINJAU MENURUT HUKUM ISLAM - Sulaiman M. Thalib (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2015)
No exaggeration to say that the indigenous Aceh synonymous with Islamictradition. Because of the majority of the Acehnese people embraced Islam andAceh is the gateway entry of Islam to Indonesia, so that customs and trdisi societyinfluenced by the values of Islam are condensed. The purpose of this study was toinvestigate the implementation Peucicap ceremony in Aceh society traditionamong indigenous (local culture) and the Sunnah of the Prophet Muhammad whois the source of Islamic law. The method used in this study is a research methodliterature to collect data and information from books, magazines, manuscripts,notes, historical accounts, documents, etc., kususnya relating to peucicap and stuffAnother related. After doing research, it can be concluded that the CeremonyPeucicap in the tradition of the people of Aceh source is the Sunnah of theProphet Muhammad called tahnik, but has been assimilated into the local cultureresulting in the development, additions and adjustments are quite varied but didnot violate Islamic law which can damage theology, Shari'ah and Islamicmorality.